The influence of company's external and internal factors to financial performance and company competitiveness on consumer good companies industry - Ahmad Nur Budi Utama; Syamsurijal Tan; Tona Aurora Lubis; Asep Machpuddin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The purpose of this study is to predict the influence model of external and internal factors of a company, starting a company's financial performance on the competitiveness of companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange. The sample of this research is 35 companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange during the period of 2016 to 2018. This research is used SEM (Structural Equation Modeling) based on component or variance based analysis known as Partial Least Square (PLS). The results of this study concluded that external factors affect the company's financial performance and company competitiveness. Internal factors also affect the company's financial performance and competitiveness but the influence of  both external factors and internal factors respectively are not able to mediate the financial performance of the company's competitiveness